Towards a biochemical characterization of the diatom pyrenoid - Oh, Zhen Guo (Nanyang Technological University, 2020)
The key photosynthetic CO2-fixing enzyme, Ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco), generally possesses a poor catalytic rate. It is also susceptible to a side-reaction with oxygen and forms dead-end inhibited complexes with sugar phosphates. Increasing the CO2 concentration at the Rubisco active site can counter these drawbacks. Most marine phytoplankton possess a carbon dioxide concentrating mechanism (CCM), which uses active transport to saturate the Rubisco active site with its gaseous substrate. A key component of this CCM is a non-membranous Rubisco compartment within the chloroplast stroma known as the pyrenoid. This study initiated a biochemical chacterization of the pyrenoid of the model diatom, Phaeodactylum tricornutum. Pyrenoid Factor 1 (Pf1) is an intrinsically disordered repeat protein that was identified through co-immunoprecipitation of P. tricornutum Rubisco and shown to localize to the pyrenoid. Pure recombinant Pf1 underwent homotypic liquid liquid phase separation (LLPS) to form condensates that specifically partitioned diatom Rubisco. Gel-shift assays involving Pf1 fragments and multiple chimeric Rubisco variants demonstrated that the proteins interact via repeated Pf1 KWSPR/Q motif and the Rubisco small subunit. These results contribute to our understanding of the convergent evolution of pyrenoid in diverse eukaryotic algae. Further definition of the components and interactions governing the assembly of the red-lineage phytoplankton pyrenoid will empower our ability to enhance carbon fixation in future crops.